Analysis of the Development Strategy for Agrotourism Taman Herbal Insani as an Educational and Recreational Tourism - Ristanti, Lilis Ari; Budi Setiawan (The Postgraduate School of Tourism Sahid Polytechnic, 2025)
Purpose: This research is to analyze the development strategy of the Taman Herbal Insani in Depok City as an educational and recreational tourism destination. Research Methods: This study uses qualitative methods with documentary collection techniques and observation. Taman Herbal Insani has significant strengths in terms of its wide collection of herbal plants and complete facilities, but has weaknesses in terms of promotion and accessibility. Taman Herbal Insani is diverse and has the potential to be developed by using a well planned development strategy, it can increase visitor appeal and attract more visitors, create memorable experiences for tourists, develop more interesting and educational activity facilities, improve service quality, and establish cooperation with educational institutions. Results and discussion: The results in this study Agrotourism Taman Herbal Insani in Depok city has great potential as a unique educational and recreational tourism destination, but it still faces several challenges. One alternative to overcome these challenges is by developing the agricultural sector combined with the tourism sector. Implication: The results of this study helps in planning sustainable development, ensuring that the park remains relevant and attractive to visitors in the long term. With the right development strategy, Taman Herbal Insani can enhance both the quality and quantity of visitors, becoming one of the popular educational and recreational tourist destinations in Depok City.